Penguatan Sekolah Ramah Anak Melalui Partisipasi Siswa - Irma Fitriana Ulfah; Tia Subekti; Muhtar Haboddin (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Student involvement in the school environment reflects the implementation of the Child-Friendly City policy. It serves as proof of the government's dedication to enforcing the Convention on the Rights of the Child and the mandate of the 1945 Constitution, particularly articles 28 and 31. Malang City approved the KLA Regional Regulation on May 14, 2024. This policy requires proper monitoring. The community service activity contributes to the supervision of implementing Child-Friendly Schools. This service promotes and strengthens student participation at SDN Tunjungsekar 4. This activity involves students in grades 1-3 as well as class teachers, lecturers, and students. Socialization is given by providing material about children, children's rights, and forms of student participation that can be done at school. Socialization activities are also followed by Question and Answer sessions and games to increase student enthusiasm. As part of this community service activity, we conducted a mapping of student participation at SD Tunjungsekar 4. The mapping results indicate that students have engaged in various activities at school, including daily duty schedules, Clean Fridays, class management competitions, and selecting extracurricular activities based on their interests, such as angklung, dance, pencak silat, and scouts. An additional form of participation is the art performance held to commemorate National Education Day, providing children with a space to unleash their creativity and self-expression. This type of participation should be continuously nurtured to enhance learning in schools and to support child-friendly education, as well as to strengthen the policies related to the development of Child-Friendly Cities.